Electroosmotic Facilitated Protein Capture and Transport through Solid‐State Nanopores with Diameter Larger than Length. Issue 11 (16th April 2020) - Zhang, Yin; Zhao, Jiabin; Si, Wei; Kan, Yajing; Xu, Zheng; Sha, Jingjie; Chen, Yunfei
Abstract: Solid‐state nanopores can be a powerful tool to investigate proteins in their native state. However, the excessive fast translocation speed of proteins causes the majority of events to remain undetected. Here, the behaviors of streptavidin (SA) transport through a solid‐state nanopore are dominated by electroosmotic flow (EOF). Experimental results show the frequency of translocation events detected by the nanopore with a diameter slightly larger than length is ≈17 times larger than that in previously reported work. Numerical simulations elucidate the enhanced frequency comes from a concave‐shape EOF in the nanopore, which provides a low water velocity region allowing for numbers of SAs moving slowly enough to be detected. However, as pore diameter increases, the maximum detectable velocity of SAs decreases due to the reduced signal‐to‐noise ratio. Moreover, it is found the SA translocation frequency slowly increases with the amplitude of voltages, and then declines at a threshold bias. This phenomenon can be attributed to the bandwidth limitation combined with the non‐linear dependence of EOF velocity in the pore central region on applied voltage. Abstract : The behaviors of streptavidin transport through a solid‐state nanopore dominated by electroosmotic flow (EOF) are studied. Experimental results show the non‐monotonic dependence of the frequency of translocation events on both pore size and applied voltage. This phenomenon can be attributed to the bandwidth limitation combined with the inhomogeneous EOF velocity distribution in the nanopore.